Antidepressant medication use before and after kidney transplant: implications for outcomes – a retrospective study. (3rd August 2017) - Lentine, Krista L.; Naik, Abhijit S.; Ouseph, Rosemary; Zhang, Zidong; Axelrod, David A.; Segev, Dorry L.; Dharnidharka, Vikas R.; Brennan, Daniel C.; Randall, Henry; Gadi, Raj; Lam, Ngan N.; Hess, Gregory P.; et al.
Summary: We examined a novel database wherein national US transplant registry identifiers were linked to records from a large pharmaceutical claims warehouse (2008–2015) to characterize antidepressant use before and after kidney transplantation, and associations [adjusted hazard ratio (aHR) 95% CI] with death and graft failure. Among 72 054 recipients, 12.6% filled antidepressant medications in the year before transplant, and use was more common among women and patients who were white, unemployed, and had limited functional status. Pre‐transplant antidepressant use was associated with 39% higher 1‐year mortality (aHR 1.39, 95% CI 1.18–1.64) and 15% higher all‐cause graft loss risk (aHR 1.15, 95% CI 1.02–1.30). More than 50% of patients who filled antidepressants pre‐transplant continued fill post‐transplant. Antidepressant use in the first year after transplant was associated with twofold higher risk of death (aHR 1.94, 95% CI 1.60–2.35), 38% higher risk of death‐censored graft failure, and 61% higher risk of all‐cause graft failure in the subsequent year. Pre‐listing antidepressant use was also associated with increased mortality, but transplantation conferred a survival benefit regardless of prelisting antidepressant use status. While associations may in part reflect underlying behaviors or comorbidities, kidney transplant candidates and recipients treated with antidepressant medications should be monitored and supported to reduce the risk of adverse outcomes.